2017
DOI: 10.1002/bip.23019
|View full text |Cite
|
Sign up to set email alerts
|

On‐demand tuned hazard free elastomeric composites: A green approach

Abstract: Rising ecological concerns and depletion of the potentially harmful environmental impacts caused by rubber products, are of prime importance in the industry. Therefore, implementation of sustainable greener materials is required to minimize the detrimental influences. In this research, we investigated the beneficial influence of naturally derived bio-resin toward the effects of association with Zinc Oxide Nanoparticles in highly dispersible silica (HDS) reinforced Natural rubber (NR)/Epoxidized Natural Rubber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…13,14 These primarily include replacing conventional ZnO with nano ZnO, zinc complexes, functionalized ZnO, and other metal oxides. 15 Because of its smaller particle size and higher surface area, nano ZnO can assist in minimizing the amount of ZnO used in rubber formulations, resulting in better dispersion in the matrix. The introduction of a new type of ZnO termed active ZnO, which has a large surface area of 30-70 m 2 /g changed the activation ability dramatically.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 These primarily include replacing conventional ZnO with nano ZnO, zinc complexes, functionalized ZnO, and other metal oxides. 15 Because of its smaller particle size and higher surface area, nano ZnO can assist in minimizing the amount of ZnO used in rubber formulations, resulting in better dispersion in the matrix. The introduction of a new type of ZnO termed active ZnO, which has a large surface area of 30-70 m 2 /g changed the activation ability dramatically.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reduced or eliminated the ZnO in rubber compounding 13,14 . These primarily include replacing conventional ZnO with nano ZnO, zinc complexes, functionalized ZnO, and other metal oxides 15 . Because of its smaller particle size and higher surface area, nano ZnO can assist in minimizing the amount of ZnO used in rubber formulations, resulting in better dispersion in the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] However, the use of ZnO is problematic because it is expensive, high density, and ecotoxic. [19][20][21] However, the use of ZnO is problematic because it is expensive, high density, and ecotoxic.…”
Section: Introductionmentioning
confidence: 99%
“…improve vulcanization kinetics, processability, and physical properties, such as abrasion resistance. [19][20][21] However, the use of ZnO is problematic because it is expensive, high density, and ecotoxic. 5,22 The Environmental Protection Agency and European Union have suggested that the use of ZnO be reduced due to its detrimental effects on aquatic organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ENR was used as a compatibilizer in organic filler filled NR composites wherein cure characteristics, tensile and dynamic mechanical properties were found to be improved Terpenoids (referred to interchangeably as terpenes) are sometimes called isoprenoids. Terpene occurs in all living organisms but attains their greatest structural and functional diversity in plants . In fact, terpene constitutes the largest and most diverse class of plant compounds .…”
Section: Introductionmentioning
confidence: 99%